Homomorphism and Anti- Homomorphism of Interval Valued Intuitionistic Fuzzy Ternary Subhemiring of a Hemiring (International Journal of Scientific Research and Management (IJSRM), 2017)
In this paper, we define the concept of Interval-Valued Intuitionistic Fuzzy Ternary Subhemiring ( IVIFTSHR) of a Hemiring and also in this note we discussed, some properties of image and pre-image of a level ternary subhemiring of IVIFTSHR with respect the Homomorphism and Anti-Homomorphism.